Metal-Free, Sustainable Synthesis of Polycaprolactone-Based Graft Copolymers Through Tandem ROP and ATRP at Ambient Temperature - Tulumcu, Zeynep; Zor, Ozge; Ciftci, Mustafa (Wiley, 2026)
A metal-free and sustainable strategy for the synthesis of graft copolymers was developed by combining ring-opening polymerization (ROP) of epsilon-caprolactone with atom transfer radical polymerization (ATRP) at ambient temperature. Polycaprolactone (PCL) backbones bearing initiating sites were first prepared and subsequently employed for ATRP of two different vinyl monomers, methyl methacrylate (MMA) and poly(ethylene glycol) methyl ether acrylate (PEGA). This tandem polymerization approach enabled the controlled preparation of well-defined PCL-g-PMMA and PCL-g-PPEGA graft copolymers without the use of transition-metal catalysts. The successful incorporation of side chains was confirmed by 1H-NMR and FT-IR spectroscopy, while molecular weight distributions were evaluated by gel permeation chromatography (GPC). Differential scanning calorimetry (DSC) revealed the influence of grafting on the thermal properties of the copolymers, and water contact angle (WCA) measurements demonstrated surface wettability changes associated with PEGA incorporation.
Keywords: ATRP; graft copolymers; metal-free polymerization; polycaprolactone; ROP